Pelaksanaan Belajar-Mengajar Dalam Situasi Pandemik Covid-19 di Sekolah Dasar dan Menengah Kota Kupang - Hemma Tinenti; Emilia Barek Ola; Yeremias Siono (VOCAT: JURNAL PENDIDIKAN KATOLIK, 2022)
The purpose of this research is to know the process of implementing on-line teaching and learning in schools during the pandemic; the reason why schools do not yet have an on-line Learning Application; and the reasons teachers cannot use online learning media. This research can also provide input for schools in dealing with technological changes that are developing in supporting the teaching and learning process as well as in dealing with pandemic conditions like today. The results showed that the implementation of teaching and learning is known that online teaching and learning and the use of applications and online learning media are in good category with an average percentage of 27.09%. It can be said that if the online Catholic teaching-learning process wants to run well, then the teachers are well prepared and equipped by the school, one of which is providing complete facilities for the online teaching-learning process, as well as providing regular training to teachers, especially in using applications. study. And teachers are also prepared through trainings to be able to make interesting teaching materials through electronic communication media.